2017
DOI: 10.1074/jbc.m116.771675
|View full text |Cite
|
Sign up to set email alerts
|

Delineating distinct heme-scavenging and -binding functions of domains in MF6p/helminth defense molecule (HDM) proteins from parasitic flatworms

Abstract: MF6p/FhHDM-1 is a small protein secreted by the parasitic flatworm (trematode) that belongs to a broad family of heme-binding proteins (MF6p/helminth defense molecules (HDMs)). MF6p/HDMs are of interest for understanding heme homeostasis in trematodes and as potential targets for the development of new flukicides. Moreover, interest in these molecules has also increased because of their immunomodulatory properties. Here we have extended our previous findings on the mechanism of MF6p/HDM-heme interactions and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 57 publications
4
23
1
Order By: Relevance
“…MF6p/HDMs are a broad family of small proteins secreted by helminth parasites [9]. Although the physiological roles of MF6p/HDMs in trematode parasites have not been clearly established, several studies suggested two interesting biological functions of this family of proteins.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…MF6p/HDMs are a broad family of small proteins secreted by helminth parasites [9]. Although the physiological roles of MF6p/HDMs in trematode parasites have not been clearly established, several studies suggested two interesting biological functions of this family of proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Although the physiological roles of MF6p/HDMs in trematode parasites have not been clearly established, several studies suggested two interesting biological functions of this family of proteins. The molecules act as heme scavengers and transporters to maintain heme homeostasis in trematode parasites, indicating an essential role in parasite survival by detoxifying the toxic free form [9,14]. Their ability to bind to LPS and prevent LPS-induced inflammation in mice as well as their ability to suppress antigen processing and presentation in macrophages also suggested an immunomodulatory role in suppressing host immune response, which facilitated prolonged parasite survival in the hosts [10-13, 36, 37].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations